Old and Sick in America : The Journey through the Health Care System - Gillick, Muriel R., 1951- (Book collections on Project MUSE., 2017)
"Since the introduction of Medicare and Medicaid in 1965, the American health care system has steadily grown in size and complexity. Muriel R. Gillick takes readers on a narrative tour of American health care, incorporating the stories of older patients as they travel from the office to the hospital to the skilled nursing facility, and examining the influence of forces as diverse as pharmaceutical corporations, device manufacturers, and health insurance companies on their "--Publisher's description.--